The Study of Modular Construction System (MCS) Application for Affordable Housing in Malaysia - Kiat Eng, Teh; Zainal, Rozlin (Research in Management of Technology and Business, 2021)
Modular Construction System (MCS) in some developed countries is defined as a Modern Method of Construction (MMC) or Offsite Fabrication (OSF). The use of robotic and automated technologies in MCS still not gain so much popularity among construction building players. This paper discusses the understanding MCS among the construction company in Malaysia, the challenge faced to adopting robotic technologies in MCS, and method improvement implementation of robotic technology in MCS among Malaysia construction industry. Qualitative and quantitative research was conducted in this research. G7 at Johor Bahru was been respondent in this research. A questionnaire (79 respondents) and a semi-structured interview (5 respondents) had participated in this research. Descriptive analysis (SPSS) and thematic analysis using in this research to analyse data have been collected from questionnaire form and interview form. From the data analysis result, most of the respondents have knowledge and understanding about the MCS. Furthermore, the cost can be the main challenge in the MCS to applying robotic technology. Also, some of the methods that have been identified can be used to improve the application of robotic technology in MCS among the G7 construction company in Johor Bahru. This research can provide the knowledge of the MCS, grasp the challenge faced in robotic technologies and understand which initiative method can overcome challenges in the MCS.